The real option value of free trade agreements - Cortázar, Gonzalo (Estudios de Economía, 2016)
The purpose of this paper is to analyze the effects of exchange rate risk in the value of bilateral and multilateral trade agreements. In order to value a bilateral trade agreement we initially consider a firm that must sell al its output in the local market. Then, we assume that the country in which the firm is located joins a bilateral trade agreement allowing the firm to redirect its output to another market whenever the level of exchange rates makes this optimal. The value of the bilateral trade agreement for the firm is then computed as the difference in firm value under both scenarios. Similarly, we value a multilateral trade agreement by computing the value of a firm that has the option to redirect its output to any among N countries. Our results indicate that volatility of exchange rates may be valuable and thus their stabilization may harm some firms. In particular it provides support to those who oppose eliminating all volatility by means of defining a single currency within these trade agreements. Our main contribution is to incorporate modern financial economics into the analysis of free trade agreements and to highlight the option value of having costs and revenues expressed in different currencies.